Romeo and Juliet - Shakespeare, William, 1564-1616 (Staged collection., 2024)
"After a chance meeting at a ball, Romeo Montague and Juliet Capulet fall desperately in love. But their families are locked in a bitter rivalry, their love forbidden. Worse still, Juliet's family already expect her to marry her suitor, Count Paris. Determined to save their love, Romeo and Juliet wed in secret. But when a fight erupts that leaves Montagues and Capulets dead, Romeo is banished from Verona, forcing Juliet to take desperate measures that spell tragedy for the star-crossed lovers"--Amazon.com.